2017
DOI: 10.1111/andr.12430
|View full text |Cite
|
Sign up to set email alerts
|

Dietary patterns and semen quality: a systematic review and meta‐analysis of observational studies

Abstract: SUMMARYA number of studies have examined the association between dietary patterns and semen quality, but the findings have been inconclusive. Herein, we conducted a systematic review and meta-analysis of observational studies to assess the association between dietary patterns and semen quality. PubMed, Cochrane library, Science direct, Scopus, Google Scholar, and ISI web of science databases were searched up to August 2016 for observational studies assessing the association between common dietary patterns and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
39
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(39 citation statements)
references
References 68 publications
0
39
0
Order By: Relevance
“…Studies assessing the effect of healthy dietary patterns, regardless of whether they were dataor hypothesis-driven, presented a positive relationship with sperm quality [25]. Healthy dietary patterns, including the DASH diet, correlated positively with the intake of foods or nutrients, which have a favourable effect on maintaining or improving semen quality [26].…”
Section: Discussionmentioning
confidence: 99%
“…Studies assessing the effect of healthy dietary patterns, regardless of whether they were dataor hypothesis-driven, presented a positive relationship with sperm quality [25]. Healthy dietary patterns, including the DASH diet, correlated positively with the intake of foods or nutrients, which have a favourable effect on maintaining or improving semen quality [26].…”
Section: Discussionmentioning
confidence: 99%
“…6,7 More recently, however, interest has shifted to focus on the role of overall diet patterns. 7,8 Although this literature is still expanding, these studies suggest that adherence to generally healthy diet patterns is…”
Section: Introductionmentioning
confidence: 99%
“…All analyses were done using the random effects model which takes the between-study variability into account. 31 The sensitivity analyses were also performed to assess the influence of each individual study on the stability of the meta-analysis results. Each time, one study was excluded to show the impact of that study on the combined effect estimate.…”
Section: Discussionmentioning
confidence: 99%
“…Studies scoring 7-10, 3-6, and 0-3 points were identified as high, moderate, and low quality, respectively. 30…”
Section: Study Qualitymentioning
confidence: 99%
See 1 more Smart Citation